2017
DOI: 10.15453/2168-6408.1352
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Instructional Technology Used in the Education of Occupational Therapy Students: A Survey Study

Abstract: The purpose of this study was to explore the type of instructional technology (IT) master's degree level occupational therapy educational programs routinely use as a part of their lecture-and laboratory-based instruction. Surveying the administrators of 121 graduate occupational therapy programs in the United States, we found that the majority of the respondents identified their program as using IT in some form for lecture-based courses, with less inclusion of IT for laboratory-based courses. Hybrid instructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…OT educators who have integrated technology into their instructional delivery recognize the current generation of students are competent users of technology and the internet (Gee, Salazar, Porter, Clark, & Peterson, 2017;Hills, Ryan, Smith, & Warren-Forward, 2012). However, some educators continue to report barriers to teaching students to utilize technology in clinical practice; these include the instructor's lack of planning time, knowledge, and access to current technology (Gee et al, 2017). A gap in the literature exists regarding specific OT instructional content on the implementation of technology in older adult client education.…”
Section: Teaching Students To Use Technology In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…OT educators who have integrated technology into their instructional delivery recognize the current generation of students are competent users of technology and the internet (Gee, Salazar, Porter, Clark, & Peterson, 2017;Hills, Ryan, Smith, & Warren-Forward, 2012). However, some educators continue to report barriers to teaching students to utilize technology in clinical practice; these include the instructor's lack of planning time, knowledge, and access to current technology (Gee et al, 2017). A gap in the literature exists regarding specific OT instructional content on the implementation of technology in older adult client education.…”
Section: Teaching Students To Use Technology In Clinical Practicementioning
confidence: 99%
“…This lack of instructional content makes it difficult for new OT faculty to integrate technology into courses, while simultaneously writing syllabi, modules, lectures, assignments, rubrics, and tests. Even experienced professors may lack the technological competency necessary to teach students to use technology in clinical practice (Gee et al, 2017). While it may not be feasible to address all concerns of instructors in the use of technology in the classroom, a concise, practical guide outlining specific ideas to integrate technology for older adults into an established OT curriculum may result in students who are more competent in implementing these strategies with their older adult clients.…”
Section: Teaching Students To Use Technology In Clinical Practicementioning
confidence: 99%
“…Such technology can address various learning preferences and create an active learning environment to keep students engaged and focused on learning. Thus, the use of technology may be helpful in promoting active learning and student engagement and satisfaction, especially as technology evolves, resulting in online interactive programs, videos, emails, podcasts, and web-based systems 11. Research has demonstrated students perceive that technology would improve their performance and facilitate their learning 12.…”
mentioning
confidence: 99%
“…Thus, the use of technology may be helpful in promoting active learning and student engagement and satisfaction, especially as technology evolves, resulting in online interactive programs, videos, emails, podcasts, and web-based systems. 11 Research has demonstrated students perceive that technology would improve their performance and facilitate their learning. 12 In addition, faculty and students alike have become comfortable with the idea that learning can effectively occur through the use of technology.…”
mentioning
confidence: 99%